THE FACTORS WHICH INFLUENCE THE EFFECTIVENESS OF SAKIP IMPLEMENTATION WITH WORK CULTURE AS MODERATING VARIABLE IN THE TEBING TINGGI MUNICIPAL GOVERNMENT - Pardede, Rejeki (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to analyse and examine the influence of SAKIP guidelines, regional government’s commitment, central government’s support, and strategic planning on the effectiveness of SAKIP implementation with work culture as moderating variable in the Tebing Tinggi Municipal Government. The research used comparative causal method. The population was the government employees who did organizing and reporting program in 31 SKPD (Regional Work Unit) in the Tebing Tinggi Municipal Government, and all of them were used as the samples, taken by using census sampling technique. Primary data were gathered by distributing 62 questionnaires to the SKPD Secretaries and the Heads of Sub-Departments of Planning and Finance in each SKPD, and 60 questionnaires were returned.  The data were processed by using Structural Equation Modeling (SEM). The result of the first hypothesis showed that SAKIP guidelines, regional government’s commitment, central government’s support, strategic planning, and work culture had positive and significant influence on the effectiveness of SAKIP implementation. The result of the hypothetical test on moderation effect showed that work culture could moderate the correlation between SAKIP guidelines and the effectiveness of SAKIP implementation and could moderate the correlation between regional government’s commitment and the effectiveness of SAKIP implementation. On the other hand, it could not moderate the correlation between, central government’s support and the effectiveness of SAKIP implementation and could not moderate the correlation between strategic planning and the effectiveness of SAKIP implementation.